Proof: Get Iterate Parent 46
Let's prove the following theorem:
if the following are true:
- expression state at time 46 = "iterate_args"
- arguments stack at time 46 = [ [
self.x
, [ 5, [ ] ] ], [ [ ], [ ] ] ] - parent stack at time 46 = [
__add__(self.x, 5)
, [ self."x" =__add__(self.x, 5)
, [ ] ] ]
then parent stack at time 47 = [ __add__(self.x, 5)
, [ self."x" = __add__(self.x, 5)
, [ ] ] ]
Proof:
Given
1 | expression state at time 46 = "iterate_args" |
---|---|
2 | arguments stack at time 46 = [ [ self.x , [ 5, [ ] ] ], [ [ ], [ ] ] ] |
3 | parent stack at time 46 = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ] |
# | Claim | Reason |
---|---|---|
1 | parent stack at time (46 + 1) = parent stack at time 46 | if expression state at time 46 = "iterate_args" and arguments stack at time 46 = [ [ self.x , [ 5, [ ] ] ], [ [ ], [ ] ] ], then parent stack at time (46 + 1) = parent stack at time 46 |
2 | parent stack at time (46 + 1) = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ] |
if parent stack at time (46 + 1) = parent stack at time 46 and parent stack at time 46 = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ], then parent stack at time (46 + 1) = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ] |
3 | 46 + 1 = 47 | 46 + 1 = 47 |
4 | parent stack at time (46 + 1) = parent stack at time 47 | if 46 + 1 = 47, then parent stack at time (46 + 1) = parent stack at time 47 |
5 | parent stack at time 47 = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ] |
if parent stack at time (46 + 1) = parent stack at time 47 and parent stack at time (46 + 1) = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ], then parent stack at time 47 = [ __add__(self.x, 5) , [ self."x" = __add__(self.x, 5) , [ ] ] ] |
Comments
Please log in to add comments